Improving Net Energy Efficiency of Dimethyl Ether Production Process by Methanol Dehydration - Permatasari, Astrid Eka; Syabila, Syalaisa Nanda; Dewi, Hly Tyas Ajeng Kartika; Zahra, Rufaidah Nilam (Journal of Chemical Engineering Research Progress, 2024)
Dimethyl ether (DME) is a source of fuel that produces clean energy for the future. Methanol can be used as a raw material for the manufacture of DME as a natural gas that is treated for synthesis. This paper evaluates how to improve net energy efficiency in DME production and how to review the net energy efficiency calculations in DME production. Methods used for production of DME are methanol dehydration, thermodynamics examination, also improving the net energy efficiency of DME with the addition of the heat exchanger (E-100), the addition of a heater (E-104) before entering a column (T-102), and moved the mixer position before the heater (E-100). By modifying the addition of a heat exchanger (E-100), heater (E-104), and changing the position of the mixer in DME production, it has been proven that it can reduce energy requirements in the dimethyl ether synthesis process from methanol and increase net energy efficiency by up to 98.83%. The results of the case study indicate that the addition heat exchanger (E-100) able to reduce the heater load after the creation process and remove the cooler (E-101) that existed before creation, then the addition of the heater (E-104) serves to reduce the load of Qcond2 and Qreb2 on columns (T-102), also the position of the mixer for the methanol recycling flow is moved before the heater (E-100) is intended to remove the heaters (E-103). Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).